2014
DOI: 10.1016/j.jallcom.2013.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution upon decomposition of the LiAlH4+LiBH4 system

Abstract: a b s t r a c tIn the present work we focus the attention on the phase structural transformations occurring upon the desorption process of the LiBH 4 + LiAlH 4 system. This study is conducted by means of manometriccalorimetric, in situ Synchrotron Radiation Powder X-ray Diffraction (SR-PXD) and ex situ Solid State Magic Angle Spinning (MAS) Nuclear Magnetic Resonance (NMR) measurements. The desorption reaction is characterized by two main dehydrogenation steps starting at 320 and 380°C, respectively. The first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
5
7
0
Order By: Relevance
“…Onset dehydrogenation temperature of LiAlH 4 reduces bỹ 50 C after milling with LiBH 4 , while that of LiBH 4 is comparable to bulk material, in agreement with the previous works of LiBH 4 eLiAlH 4 [18,19]. It was reported that by compositing LiBH 4 with Al or LiAlH 4 , although reduction of onset dehydrogenation temperature of LiBH 4 was not achieved, reversibility of LiBH 4 was improved due to the formation of AlB 2 instead of amorphous boron (a-B) [17,18].…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Onset dehydrogenation temperature of LiAlH 4 reduces bỹ 50 C after milling with LiBH 4 , while that of LiBH 4 is comparable to bulk material, in agreement with the previous works of LiBH 4 eLiAlH 4 [18,19]. It was reported that by compositing LiBH 4 with Al or LiAlH 4 , although reduction of onset dehydrogenation temperature of LiBH 4 was not achieved, reversibility of LiBH 4 was improved due to the formation of AlB 2 instead of amorphous boron (a-B) [17,18].…”
Section: Resultssupporting
confidence: 91%
“…For milled LiBH 4 eLiAlH 4 , separately two-step decomposition of LiAlH 4 and LiBH 4 in the ranges of 100e200 and 300e500 C releases totally 8.7 wt.% H 2 ( Fig. 3(C)), approaching to the previous work of Soru et al [19]. With respect to theoretical hydrogen storage capacity of LiBH 4 eLiAlH 4 composite of 10.12 wt.% based on equation (7) [19], 86% of theoretical value is obtained from milled LiBH 4 eLiAlH 4 .…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations